Impact of sampling and storage stress on the recovery of airborne SARS-CoV-2 virus surrogate captured by filtration. Issue 9 (27th August 2021) - Myers, Nirmala T.; Han, Taewon T.; Li, Mei-Ling; Brewer, Gary; Harper, Martin; Mainelis, Gediminas
Abstract: Environmental air sampling of the SARS-CoV-2 virus in occupational and community settings is pertinent to reduce and monitor the spread of the COVID pandemic. However, there is a general lack of standardized procedures for airborne virus sampling and limited knowledge of how sampling and storage stress impact the recovery of captured airborne viruses. Since filtration is one of the commonly used methods to capture airborne viruses, this study analyzed the effect of sampling and storage stress on SARS-CoV-2 surrogate virus (human coronavirus OC43, or HCoV-OC43) captured by filters. HCoV-OC43, a simulant of the SARS-CoV-2, was aerosolized and captured by PTFE-laminated filters. The impact of sampling stress was evaluated by comparing the RNA yields recovered when sampled at 3 L/min and 10 L/min and for 10 min and 60 min; in one set of experiments, additional stress was added by passing clean air through filters with the virus for 1, 5, and 15 hr. The impact of storage stress was designed to examine RNA recovery from filters at room temperature (25 °C) and refrigerated conditions (4 °C) for up to 1 week of storage. To our knowledge, this is the first report on using HCoV-OC43 aerosol in air sampling experiments, and the mode diameter of the virus aerosolized from the growth medium was 40–60 nm as determined by SMPS + CPC system (TSI Inc.) and MiniWRAS (Grimm Inc.) measurements. No significant difference was found in virus recovery between the two sampling flow rates and different sampling times (p > 0.05). However, storage at room temperature (25 °C) yielded ∼2x less RNA than immediate processing and storage at refrigerated conditions (4 °C). Therefore, it is recommended to store filter samples with viruses at 4 °C up to 1 week if the immediate analysis is not feasible. Although the laminated PTFE filter used in this work purposefully does not include a non-PTFE backing, the general recommendations for handling and storing filter samples with viral particles are likely to apply to other filter types.